2016
DOI: 10.1099/jgv.0.000359
|View full text |Cite
|
Sign up to set email alerts
|

Balance of RNA sequence requirement and NS3/NS3a expression of segment 10 of orbiviruses

Abstract: Orbiviruses are insect-transmitted, non-enveloped viruses with a ten-segmented dsRNA genome of which the bluetongue virus (BTV) is the prototype. Viral non-structural protein NS3/NS3a is encoded by genome segment 10 (Seg-10), and is involved in different virus release mechanisms. This protein induces specific release via membrane disruptions and budding in both insect and mammalian cells, but also the cytopathogenic release that is only seen in mammalian cells. NS3/NS3a is not essential for virus replication i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…In addition, differences in tissue culture susceptibility observed between the three variants (and in comparison with BTV-25 and 26) raise questions pertaining to the nature of the viral genetic control(s) affecting transmission and susceptibility. Moreover, recent studies demonstrated that interactions between BT viral proteins are crucial in terms of tissue tropism and particularly in insect cells (Feenstra, Drolet, Boonstra, & van Rijn, 2015;Feenstra, van Gennip, Schreuder, & van Rijn, 2016;Nunes et al, 2014 andPullinger et al, 2016). Reverse genetics using mono-reassortants of BTV-26 genes in a BTV-1 background has been able to provide answers for some of these (Pullinger et al, 2016).…”
Section: Rt-qpcr Resultsmentioning
confidence: 99%
“…In addition, differences in tissue culture susceptibility observed between the three variants (and in comparison with BTV-25 and 26) raise questions pertaining to the nature of the viral genetic control(s) affecting transmission and susceptibility. Moreover, recent studies demonstrated that interactions between BT viral proteins are crucial in terms of tissue tropism and particularly in insect cells (Feenstra, Drolet, Boonstra, & van Rijn, 2015;Feenstra, van Gennip, Schreuder, & van Rijn, 2016;Nunes et al, 2014 andPullinger et al, 2016). Reverse genetics using mono-reassortants of BTV-26 genes in a BTV-1 background has been able to provide answers for some of these (Pullinger et al, 2016).…”
Section: Rt-qpcr Resultsmentioning
confidence: 99%
“…Previously, RG for BTV using exclusively in vitro synthesized capped run-off RNA transcripts, have resulted in reassortants, mutants and variants with spontaneously introduced changes during rescue [ 27 , 40 ]; [ 11 , 33 ]. On the other hand, several modifications appeared not viable [ 32 , 35 , 40 ]. Here, expression plasmids with optimized ORFs of VP1, 3, 4, 6, and NS1 and 2 of BTV6/net08 were successfully used (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the success rate for rescue of mutants and reassortants, the most optimal system is the combination of all seven expression plasmids with optimized ORFs and capped RNA transcripts for the second transfection. BTV1 and BTV8 variants were generated using BTV6 based ORF-optimized expression plasmids [ 35 ], and virulent AHSV5 was similarly recovered with AHSV4LP based expression plasmids (published elsewhere). We propose that one set of expression plasmids of the respective orbivirus species in combination with a set of ten even uncapped run-off RNA transcripts will be sufficient to quickly recover new orbivirus variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation